GAMBARAN PENGGUNAAN OBAT PADA PASIEN INFEKSI SALURAN PERNAPASAN AKUT DI KLINIK PRATAMA ASTY SUKOHARJO - Nabilah Rarayanthi. A; Khotimatul Khusna; Risma Sakti Pambudi (Universitas Pahlawan Tuanku Tambusai, 2022)
Acute Respiratory Infection (ARI) is an acute infectious disease that attacks one or more parts of the respiratory tract from the nose (upper tract) to the alveoli (lower tract). The primary therapy for ARI patients is antibiotic therapy and supportive therapy. This study aims to determine the use of drugs in patients with acute respiratory infections at the Pratama Asty Clinic Sukoharjo. The research is descriptive and data collection is done retrospectively. Sampling used the slovin formula with 95 medical records. This research was conducted in January-June 2021. Data analysis used descriptive analysis and presented in tables and percentages. The results showed that the use of drugs for acute respiratory infections at the Pratama Asty Clinic Sukoharjo the use of drugs based on the most widely used drug class, namely the antibiotic group, amounting to 21.82% with the type of antibiotic used the most, namely cefadroxil as much as 11.16%. The most widely used supporting therapy is the combination drug group with a total of 18.03% with the type of drug calortusin amounting to 6.85%. The multivitamin group was 18.03% with the type of multivitamin boost drug as much as 8.88%. The class of corticosteroid drugs was 18.28% and the type of dexamethasone was 9.40%. The conclusion of this study shows that the description of drug use in ARI patients at the Pratama Clinic Asty Sukoharjo using antibiotic therapy with the addition of supporting therapy as much as 90.5% and the results obtained are patients who only use supportive therapy without antibiotics as much as 9.5%.